2015 IEEE 15th International Conference on Environment and Electrical Engineering (EEEIC) 2015
DOI: 10.1109/eeeic.2015.7165428
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of useful energy from lost human power in gymnasium

Abstract: Human powered gyms are ones in which equipment can be used to generate electricity. Since the concept of a green or sustainable gym is recent, the potential of cardio equipment like treadmills, stationary bikes and rowing machines in generating energy are discussed in this paper. The power generated in a typical human powered gym, based on the equipment already existing in the market is analyzed. The amount of carbon dioxide emissions saved and the payback period for implementing this gym are also estimated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…In the specific case of fitness equipments used in gymnasiums, previous studies showed that is possible to harvest up to 30 W of power directly from a switch-mode converter connected to an exercise bike [8], [16], and gymnasiums can potentially become energy-producing facilities [9], [17]. Assuming that will be possible to instrument fitness equipments with energy generators, we are going to demonstrate that the power consumption of the proposed system is (i) lower than the expected production of free energy and (ii) in extreme cases, it can work for more than 8 hours on a battery.…”
Section: B Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific case of fitness equipments used in gymnasiums, previous studies showed that is possible to harvest up to 30 W of power directly from a switch-mode converter connected to an exercise bike [8], [16], and gymnasiums can potentially become energy-producing facilities [9], [17]. Assuming that will be possible to instrument fitness equipments with energy generators, we are going to demonstrate that the power consumption of the proposed system is (i) lower than the expected production of free energy and (ii) in extreme cases, it can work for more than 8 hours on a battery.…”
Section: B Energy Consumptionmentioning
confidence: 99%
“…In addition to photovoltaic systems that are the most mature renewable energy technology employed in embedded systems, other energy sources have been studied and many smart solutions have been proposed, for example thermal energy scavengers are under investigation in the automotive [6] and data center cooling [7] sectors, while energy harvesting from human motion has been studied and demonstrated through experiments with fitness equipments by a number of research groups (for example in [8], [9]). This last technology is currently in use to recharge smartphones and laptops in airports with state-of-art bike-powered recharge stations [10].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of energy wasted during these recreational activities has been proposed and applied on a small scale [5]. In this context, gyms, sports centers consume electricity not only to power equipment such as treadmills, bicycles, ellipticals, but also to satisfy the comfort of their customers, such as sound equipment or televisions, adequate lighting and air conditioning systems [1]. The energy people spend doing exercises in the gym is lost in the form of heat, and this lost energy could be converted into a useful form of energy.…”
Section: Introductionmentioning
confidence: 99%
“…The energy people spend doing exercises in the gym is lost in the form of heat, and this lost energy could be converted into a useful form of energy. Some studies show that there are several sustainable gyms around the planet, many of them installed within universities [1]. .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation